Cockayne syndrome mutation in XPG activate the integrated stress response - Danhui Zhang; Max Hartmann; Zhouli Cao; Gaojie Zhu; Gregoire Najjar; Cagatay Günes; Steffen Emmert; Karin Scharffetter-Kochanek; Sebastian Iben (Human Genetics, 2026)
Xeroderma pigmentosum (XP) and Cockayne syndrome (CS) are diseases provoked by mutations in multifunctional proteins that are involved in DNA repair. DNA-repair deficiency explains the high cancer incidence of XP, whereas cancer-free CS, characterized by growth retardation, neurological degeneration, and premature aging does not present as a classical DNA-repair deficiency disorder. Here, we compared a severe combined XP/CS case provoked by XPG -mutation with an XP “only” patient cell line caused by mutation in the same XPG gene to carve out the pathogenic cellular disturbances that provoke CS. We identified RNA polymerase I transcription and rRNA maturation defects, a highly phosphorylated eukaryotic initiation factor 2 alpha (eIF2alpha), and a shift from cap- to internal ribosomal entry site (IRES) translation, indicating an activated integrated stress response in CS. Disturbances in ribosomal biogenesis and translational control might thus contribute to the development of CS.

Perspectives: State of national forest damage survey programmes in Europe and ways toward improved harmonization and data sharing - Tomáš Hlásny; Michaela Perunová; Roman Modlinger; Max Blake; Gediminas Brazaitis; György Csóka; Maarten de Groot; Mihai-Leonard Duduman; Massimo Faccoli; Margarita Georgieva; Georgi Georgiev; Wojciech Grodzki; et al. (Forest Ecology and Management, 2025)

The Spectrum of Peripheral-Vestibular Deficits and Their Change Over Time in CANVAS/RFC1-Related Ataxia Systematic Review and Meta-Analysis of Quantitative Head-Impulse Testing - Maja Szymanska Heydel; Felix Heindl; Annette Hartmann; Max Borsche; Andreas Traschütz; Dominik Straumann; Michael Strupp; Alexander Andrea Tarnutzer (The Cerebellum, 2025)
Cerebellar ataxia, neuropathy, vestibular-areflexia syndrome (CANVAS) has been linked to biallelic intronic repeat-expansions in RFC1 . Video-head-impulse testing (vHIT) offers a quantitative assessment of the angular vestibulo-ocular reflex (aVOR) of all three canals. We evaluated patterns of peripheral-vestibular impairment, its change over time and evaluated correlations with other parameters. PubMed/Embase were searched for articles reporting vHIT in patients with CANVAS/RFC1-related ataxia. A multiple linear-regression model was used to analyse relationships between vHIT-gains and clinical parameters (age, disease duration, sex, biallelic RFC1 expansion). A special focus was put on sequential vHIT in individual patients. 23/64 studies met inclusion criteria; additional 13 studies were identified through reference screening. Twenty-five studies reported individual vHIT-gains and demographic data, suitable for quantitative analysis. Substantial aVOR-gain reductions were found for horizontal (0.32 ± 0.02, n = 146 patients), anterior (0.39 ± 0.03, n = 27) and posterior (0.29 ± 0.03, n = 27) canals. Linear regression showed an association between horizontal vHIT-gains ( n = 146 patients; range of gain: 0-1.3) and disease duration (range: 0–444 months, coef. =-0.0048, p = 0.031) and male sex (coef. =-0.1604, p < 0.001). A decline in horizontal-canal vHIT-gains at least one side over time was noted in 15/21 patients after a mean follow-up time of 33.4 ± 10.7 months. vHIT is a potential biomarker for monitoring progression of CANVAS/RFC1-related ataxia. The significant association between reduced vHIT-gains and disease duration, and their intra-individual decline over time emphasize that impairment of the aVOR reflects the underlying neurodegenerative disease process. Multi-centre prospective studies are needed for systematic early screening and longitudinal validation as outcome for future targeted therapy trials.

Partitioning the influence of host specificity in amphibian populations threatened by multiple emerging infectious diseases - Arik M. Hartmann; Kimberly Sash; E. Pierson Hill; Natalie M. Claunch; Max L. Maddox; Sarah McGrath-Blaser; Cory C. McKinstry; Robert J. Ossiboff; Ana V. Longo (Biological Conservation, 2024)

C-met activation is necessary but not sufficient for liver colonization by B16 murine melanoma cells - Shuo Lin; Dario Rusciano; Patrizia Lorenzoni; Guido Hartmann; Walter Birchmeier; Silvia Giordano; Paolo Comoglio; Max M. Burger (Clinical & Experimental Metastasis, 1998)